2022
DOI: 10.3390/biology11050760
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated ADAMTS1 Incorporating A2M Contributes to Tumorigenesis and Alters Tumor Immune Microenvironment in Lung Adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) still holds the most dreadful clinical outcomes worldwide. Despite advanced treatment strategies, there are still some unmet needs. Next-generation sequencing of large-scale cancer genomics discovery projects combined with bioinformatics provides the opportunity to take a step forward in meeting clinical conditions. Based on in-house and The Cancer Genome Atlas (TCGA) cohorts, the results showed decreased levels of ADAMTS1 conferred poor survival compared with normal parts. Gene set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…According to the authors, HCCP (characterised by the increased expression of A2M) had significant anti-migration efficacy and may be considered a novel therapeutic agent for cancer treatment [34]. In both in vitro and in vivo studies, Lee et al [35] showed that the downregulation of A2M and decreased A2M protein expression levels were positively correlated with decreased ADAM metallopeptidase with thrombospondin type 1 motif 1 (ADAMTS1). Moreover, bioinformatics analyses suggest that both A2M and ADAMTS1 expressions are correlated with more aggressive phenotypes of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, HCCP (characterised by the increased expression of A2M) had significant anti-migration efficacy and may be considered a novel therapeutic agent for cancer treatment [34]. In both in vitro and in vivo studies, Lee et al [35] showed that the downregulation of A2M and decreased A2M protein expression levels were positively correlated with decreased ADAM metallopeptidase with thrombospondin type 1 motif 1 (ADAMTS1). Moreover, bioinformatics analyses suggest that both A2M and ADAMTS1 expressions are correlated with more aggressive phenotypes of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…A2M was shown to play a role in activating the epithelial-mesenchymal transition (EMT) and promoting metastasis in lung adenocarcinoma. A2M expression was negatively correlated with patients' overall survival [35]. Zhang and collaborators described A2M downregulation in intrahepatic cholangiocarcinoma (ICC) compared to normal bile duct tissue, suggesting this gene's potential utility as an adverse prognostic factor [25].…”
Section: Discussionmentioning
confidence: 99%
“…In various tumor tissues, these five complement-related genes were produced by different cells and ultimately affect tumor progression. For example, the overexpression of DOCK4 has been shown to promote migration and invasion in prostate cancer cells ( 39 ), APOBEC3G has been shown to promote colorectal liver cancer metastasis by suppressing mir-29-mediated matrix metalloproteinase-2 inhibition ( 40 ), ADAMTS1 and A2M downregulation has been shown that activating epithelial-mesenchymal transition and altering the immune microenvironment to promote lung adenocarcinoma metastasis ( 41 ), NOTCH4 has been shown to have pro-proliferative, anti-apoptotic, and pro-migratory effects on lung adenocarcinoma cells ( 42 ), and COL4A2 has been shown to activate the RhoA/ROCK pathway to promote the invasion and migration of chicken hepatocellular carcinoma cell line (LMH) cells ( 43 ). These previous studies validate the reliability of our established model to some extent.…”
Section: Discussionmentioning
confidence: 99%